“CHRIST AND THE BRAZILIAN REVOLUTIONARY PROCESS”: RELIGION, POLITICS, HUMAN RIGHTS - Matos, Marcus V. A. B. De; Vieira-Souza, Priscila (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
This paper presents the first findings of a research project in Human Rights & Religion. It discusses the main historical sources available and their potential legal, social and political impact. This is a memory & truth project that focus on the history of religious leaders who were arrested and persecuted for their opinions and analyses their struggle for human liberation and democracy. Most of them were accused under anti-communist legislation, because of their theological concerns about social justice. In this short article we will investigate a few outcomes and findings about the 1962 Brazilian North-eastern Conference whose title was shocking to both political and ecclesiastical authorities of the time: “Christ and the Brazilian revolutionary process” – a conference that reshaped the borders between human rights and religion in the 1960s, by changing the understanding of church and society relations in Latin America.